Whither economic complexity? A new heterodox economic paradigm or just another variation within the mainstream?. (2017) - Heise, Arne
Although neoclassical economics still remains the 'normal science' providing the foundation for economic education, there is a growing demand within and without the scientific community for a major overhaul of economics - a longstanding demand by heterodox economists. Complexity economics claims to be at the spotlight of this demand for 'new economic thinking'. This paper analyses the paradigmatical features of complexity economics, placing it along the heterodox-orthodox divide in order to explain its impact on the evolution of economics.